2003
DOI: 10.1038/sj.gt.3301864
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of p21WAF1/CIP1 in adenovirus vector transfected human primary hepatocytes prevents apoptosis resulting in improved transgene expression

Abstract: Replication-deficient adenovirus (Ad vector) is one of the most effective gene transfer systems. However, its employment in human gene therapy trials is hampered by Ad vector associated cytotoxicity and induction of apoptosis of the infected cells. Here, we identify one underlying mechanism as uncoupling of S phase and mitosis of the cell cycle leading to apoptosis and decline of transgene expression. Moreover, we demonstrate a strategy to avoid Ad vector associated cytotoxicity and induction of apoptosis in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…As NFkB is one of the transcription factors identified to be activated by p21 and as the RSV promoter driving a 1 -AT expression contains, besides C/ EBP and YY1 binding sites, RelA/NFkB responsive elements, it appears likely that the observed overexpression occurs through this mechanism. 23,24 This view is supported by the fact that the co-expression of p21 had an equally positive effect on RSV-and CMV-driven bgalactosidase expression (see Figure 5 in Wolff et al 5 ) and CMV has been proven to be activated by p21 18 . Further backing is provided by the varying efficiency in the a 1 -AT expression in HeLa and A549 despite similar p21 expressions (see Figure 1).…”
Section: Co-expression Of P21 In Adenoviral Vector a Schumacher Et Almentioning
confidence: 94%
See 4 more Smart Citations
“…As NFkB is one of the transcription factors identified to be activated by p21 and as the RSV promoter driving a 1 -AT expression contains, besides C/ EBP and YY1 binding sites, RelA/NFkB responsive elements, it appears likely that the observed overexpression occurs through this mechanism. 23,24 This view is supported by the fact that the co-expression of p21 had an equally positive effect on RSV-and CMV-driven bgalactosidase expression (see Figure 5 in Wolff et al 5 ) and CMV has been proven to be activated by p21 18 . Further backing is provided by the varying efficiency in the a 1 -AT expression in HeLa and A549 despite similar p21 expressions (see Figure 1).…”
Section: Co-expression Of P21 In Adenoviral Vector a Schumacher Et Almentioning
confidence: 94%
“…These data corroborate and extend earlier results, in which co-infection of an Ad vector expressing p21 with a second vector coding for a gene of interest augmented the expression from this second Ad vector. 5 In that study, the beneficial effect of p21 was ascribed to its function as a cell cycle regulator that counteracts Ad vector-mediated cell cycle dysregulation and cytotoxicity in infected cells. In this study, however, no cytotoxicity and vector-induced aberrant cell cycle profiles were observed.…”
Section: Co-expression Of P21 In Adenoviral Vector a Schumacher Et Almentioning
confidence: 99%
See 3 more Smart Citations